From Reactive to Predictive: Exploring GenAI as a Future Framework for Sustainable Property Maintenance in Namibia’s Public Housing Sector - Filippus Henok; Mart-Mari Els (SureBuilt Series, 2026)
South Africa shoopalah092@gmail.com This mixed-methods case study investigates property maintenance practices at the Keetmanshoop State Hospital Nurses Home in Namibia. Data from semi-structured interviews, questionnaires, and descriptive statistics reveal predominantly reactive practices, resulting in frequent breakdowns, prolonged repairs, and low tenant satisfaction. Challenges include fragmented planning, inadequate funding, and limited expertise. The study advocates a shift toward proactive and preventive maintenance through scheduled programmes, training, and technology-enabled systems. Rather than being an actual system, Generative Artificial Intelligence (GenAI) is suggested as a future application for data-driven decision-making and predictive maintenance. In the context of Agenda 2063 and sustainable housing discussions, the study suggests combining digital technologies with facilities management and presents a conceptual framework enabled by GenAI to assist tenant-centered, efficient, and resilient public housing maintenance in developing nations. By analysing operational bottlenecks at the municipal and institutional levels, the research highlights how traditional facilities management frameworks fail to keep pace with accelerating infrastructure decay. Modernising this sector requires addressing chronic funding deficiencies through strategic public-private partnerships, alongside institutionalising specialised technical training to build local capacity. Furthermore, leveraging GenAI-driven platforms enables automated work-order generation, intelligent resource allocation, and real-time tenant feedback processing, directly aligning local infrastructure strategies with global sustainability agendas. By establishing a scalable digital blueprint, this research provides healthcare administrators and public housing authorities in developing nations with an actionable roadmap. Transforming neglected public quarters into sustainable, resilient living environments ultimately safeguards public health investments, enhances tenant well-being, and supports the broader socio-economic goals outlined in Africa’s Agenda 2063. Ranking the Determinants of Adaptive Reu